RESUMPTION OF HOSPITAL ACCREDITATION IN THE ‘POST-COVID-19 PANDEMIC’ ERA: LEADERSHIP PERSPECTIVES - Treib, Julia Nogueira; Rodrigues, Nicole Hertzog; Barbosa, Amanda da Silveira; Guardalupe, Jéssica Azevedo; Magalhães, Ana Maria Müller de; Oliveira, João Lucas Campos de (Cogitare Enfermagem, 2024)
Objective: To understand leaders' perspectives on the resumption of the Hospital Accreditation process in the context of the "post-pandemic" of COVID-19. Method: A qualitative case study was carried out in a large university hospital in Porto Alegre (RS), Brazil. Data was collected from 10 strategic leaders from August to September 2022 through a semi-structured interview. Thematic Content Analysis was used. Results: Three categories emerged: "Hospital changes and strategies demanded by the COVID-19 pandemic"; "Quality management and patient safety challenges arising from the pandemic context"; and, "Managing the resumption of the post-pandemic Hospital Accreditation process". Conclusion: The COVID-19 health crisis has imposed obstacles on previously well-established processes. The leadership recognized the exhaustion of the teams and worked to motivate people and spread the information necessary for the success of the quality recertification.